2006
DOI: 10.3102/0091732x030001065
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 3: Learning in Inclusive Education Research: Re-mediating Theory and Methods With a Transformative Agenda

Abstract: In theory, inclusive education is about all students and focuses on student presence, participation, acceptance, and achievement. In practice, inclusive education is multiplicity of discourses and practices. Historically, inclusive education is situated within waves of evolution.The first wave saw the establishment of general rights for children with disabilities, but some children-especially those with behavioral problems and severe intellectual disabilitiesremained unrecognized outsiders in schools and schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 72 publications
1
60
0
16
Order By: Relevance
“…In a recent review of the research on inclusive education, Artiles et al (2006) argued for a transformative agenda that includes a focus on the role of power in teacher and student lives; an understanding of how inclusive schools make the learning of social divisions in practice ubiquitous; and an analysis of what we are including disabled students into. They conclude that this will add 'another layer in the definition of future inclusive education work, namely an attention to equity and social justice' (Artiles et al 2006, 100).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review of the research on inclusive education, Artiles et al (2006) argued for a transformative agenda that includes a focus on the role of power in teacher and student lives; an understanding of how inclusive schools make the learning of social divisions in practice ubiquitous; and an analysis of what we are including disabled students into. They conclude that this will add 'another layer in the definition of future inclusive education work, namely an attention to equity and social justice' (Artiles et al 2006, 100).…”
Section: Resultsmentioning
confidence: 99%
“…RTLB need to support teachers to make changes so that the curriculum is accessible to all students and participation and achievement are improved. They also need to support structural change in schools and classrooms so that the diverse needs of students are met in regular classrooms (Artiles, Kozleski, Dorn, & Christensen, 2006;Thomson, et al, 2003). However, two-thirds of the special education teachers appointed as RTLB had either taught students with special needs in segregated settings or had worked as itinerant teachers who withdrew students from regular classrooms for individualised instruction (practices consistent with mainstreaming).…”
Section: Context Of Studymentioning
confidence: 97%
“…As recent research has demonstrated, the development of inclusive practices is a multi-faceted endeavour which must take European Journal of Special Needs Education 513 account of classrooms as communities with complex relationships between all members (Artiles et al 2006;Kershner 2009;Kozleski and Waitoller 2010;Thomas 2012). It seems essential, therefore, to shift the focus of attention away from individuals identified as having special needs and disabilities, and to take careful account of the experiences of everyone in a class, so that teachers are encouraged to develop 'approaches to inclusive practice which are about all children' (Allan 2010, 206).…”
Section: Final Reflectionsmentioning
confidence: 99%